Study of Domestic Sewage Treatment Using Aquatic Macrophyte Duckweed (Lemna minor) - KURAISHI, M.A.; SHARMA†, SUNIL (Asian Journal of Chemistry, 2010)
In this study, laboratory scale experiments on duckweed covered domestic sewage were carried out to evaluate the removal efficiency of duckweed species Lemna minor as a domestic wastewater stripper. The outdoor experiments were conducted in 4 mini ponds at Jodhpur. The physico-chemical properties of domestic wastewater were evaluated before and after inoculation of culture for wastewater quality improvement. Various parameters namely pH, DO, TSS, TDS, turbidity, BOD, COD, total nitrogen and total phosphorus were analyzed for varying detention periods. The result indicated treated effluent suitability for irrigation reuse purpose.